Teaching Entrepreneurship to Postgraduates - McGrath, Kate (New Zealand Science Review, 2014)
​Teaching, Entrepreneurship and Postgraduate, separately and collectively embrace very broad areas, so based only on the title of Colin Jones’ latest book, exactly what you are going to get with this monograph is anyone’s guess. Jones’ focus is on the one hand very narrow and specific (mature post-graduate students studying a business school entrepreneurship programme) while simultaneously he espouses his generic teaching philosophy for guiding students in ‘World 2.0’.